Estimation of production cost for Indian artisanal sour buttermilk powder - MANIK, SUBHADIP; Meena, Ganga Sahay; Khetra, Yogesh; Singh, Ashish Kumar; Singh, Richa; Arora, Sumit; H. V. , Raghu (Indian Journal of Dairy Science, 2025)
The present investigation was aimed to estimate the production cost of Indian artisanal sour buttermilk powder that contains 53% protein. Additionally, it exhibits numerous techno-functional properties such as “instant” in wettability (3 s), excellent flowability (angle of repose=28.36º), water binding capacity (4.34 g/ g of protein) and excellent emulsification stability (80.70%) along with essential amino acids, fatty acids and antioxidants. Beside process standardization for the production of Indian artisanal sour buttermilk powder, this study aimed to estimate its production cost with a numerous assumption. Main assumption was production of 1260.12 tons of Indian artisanal sour buttermilk powder in 300 days. Numerous heads such as raw material, packaging material, land and building, manufacturing, utility, manpower, marketing and distribution etc. were taken as a crucial factor during estimation of total production cost of Indian artisanal sour buttermilk powder. The calculated cost for 500 g pack and 1 Kg pack of this powder was Rs. 424.14 and Rs. 212.07, respectively.